If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + g = -30 Solving 23 + g = -30 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + g = -30 + -23 Combine like terms: 23 + -23 = 0 0 + g = -30 + -23 g = -30 + -23 Combine like terms: -30 + -23 = -53 g = -53 Simplifying g = -53
| 2x+4+3x=21 | | (5-x)(7+3x)= | | 5x-2+3x=6 | | 14^x=1/196 | | K-3m=10-2(m-7) | | 2x+3x+x=26 | | 1+4j= | | -40=-8y | | 4x-16=18x-8 | | 9+49=26 | | W=-18+2w | | C(x)=0.04x^2-8.504x+25302 | | t+207=418 | | 6h+1=181 | | 0.75*0.6*x+x=1 | | K+119=1008 | | 3(2x-5)-x=5x-15 | | 2c+4=9 | | 2m+27=47 | | 2(2x+5)=6x-20 | | 3f+14=26 | | b+3=b-7 | | x-6=(-3x)+10 | | 2y-12=2 | | 2(6x+21)=4x+106 | | W+6=2(w-6)1 | | 2(2m+1)=10 | | 4x+10=3x+18 | | -6x+-1y=-58 | | x+8y=44 | | x-13=23-32 | | 7s-2=4(s+2) |